Continuous Variation in an Aposematic Pattern Affects Background Contrast, but Is Not Associated With Differences in Microhabitat Use - Yeager, Justin; Barnett, James B. (Frontiers in Ecology and Evolution, 2022)
Variation in aposematic signals was once predicted to be rare, yet in recent years it has become increasingly well documented. Despite increases in the frequency with which polytypism and polymorphism have been suggested to occur, population-wide variance is rarely quantified. We comprehensively sampled a subpopulation of the poison frog Oophaga sylvatica, a species which is polytypic across its distribution and also shows considerable within-population polymorphism. On one hand, color pattern polymorphism could be the result of multifarious selection acting to balance different signaling functions and leading to the evolution of discrete sub-morphs which occupy different fitness peaks. Alternatively, variance could simply be due to relaxed selection, where variation would be predicted to be continuous. We used visual modeling of conspecific and heterospecific observers to quantify the extent of within population phenotypic variation and assess whether this variation produced distinct signals. Despite considerable color pattern variation, we found that variance could not be partitioned into distinct groups, but rather all viewers would be likely to perceive variation as continuous. This begs the question whether color pattern variation could be adapted to chosen microhabitats, enhancing signal contrast and shaping intra- or interspecific behaviors. Similarly, we found no evidence that frog color pattern contrast was either enhanced or diminished in the frogs’ chosen microhabitats compared to alternative microhabitat patches throughout their environments. Within population phenotypic variance therefore does not seem to be indicative of strong selection maximizing signal efficacy, but rather more likely divergent due to weak purifying selection, or neutral processes, on a signal that is highly salient to conspecifics and predators.